Effect of metformin on the level of aqueous humor inflammatory cytokines in patients with cataract - Jiaxi Li; Jiarui Yang; Ziyuan Liu; Xuemin Li (Scientific Reports)
Abstract This study investigated the content of inflammatory cytokines in the aqueous humor (AH) of cataract patients with type 2 diabetes (T2DM) and explored the effect of metformin on the level of cytokines. AH was collected from patients undergoing phacoemulsification and intraocular lens implantation in Peking University Third Hospital. Levels of cytokines were measured by Cytometric Bead Assay (CBA) Flex Set. Differences in level of AH cytokines were compared between patients using metformin and non-metformin medicine as blood sugar control drug for T2DM and age-related cataract patients without T2DM. A total of 67 patients were included, including 19 healthy controls, 33 patients in the metformin group, and 15 patients in the non-metformin group. The results showed that IL-6 levels were significantly higher in the non-metformin group than the metformin group and the healthy control group (p = 0.019 and 0.014, respectively). IFN-γ levels were also significantly higher in the non-metformin group than the metformin group and the healthy control group (p = 0.031 and 0.003, respectively). The levels of IL-10 in non-metformin group were significantly higher than those in the healthy control group (p = 0.008), whereas the levels of IL-10 showed no significant difference between metformin group and healthy controls. Metformin can reduce the level of cytokines in AH to a certain extent in cataract patients combined with T2DM. It is suggested that metformin may have preventive and therapeutic effects on the development of age-related cataract.